2009
DOI: 10.3844/ajbbsp.2009.180.183
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Propolis from Different Regions in Java and their Cytotoxic Activity

Abstract: Problem statement: Propolis samples from tropical zones, such as Java (Indonesia) with its vast biodiversity, have become a subject of increasing scientific and economic attention. The association of the chemical composition of propolis from different geographic regions with cytotoxic activities lead to the identification of active principles, a fundamental tool to achieve standardization of this bee product. Approach: The purpose of this research was evaluate the quality of propolis collected at different pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For example, Brazilian green propolis displayed antiproliferative effect on lung cancer cell lines (A549), but it did not suppress the growth of Vero cells [53]. In addition, propolis collected from different geographic regions of Indonesia showed cytotoxicity against tumor cell lines (T47D, MCF-7, and HeLa) and did not inhibit the growth of Vero cells [54]. Moreover, many studies demonstrated that the encapsulation of drug into PLGA nanoparticles can decrease the toxicity of drug.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Brazilian green propolis displayed antiproliferative effect on lung cancer cell lines (A549), but it did not suppress the growth of Vero cells [53]. In addition, propolis collected from different geographic regions of Indonesia showed cytotoxicity against tumor cell lines (T47D, MCF-7, and HeLa) and did not inhibit the growth of Vero cells [54]. Moreover, many studies demonstrated that the encapsulation of drug into PLGA nanoparticles can decrease the toxicity of drug.…”
Section: Discussionmentioning
confidence: 99%
“…GC-MS analysis has shown that Ethanolic propolis extract (EEP) contained (percentage of total ion current): Benzoic acid 0.41, Phenylic acid 95.62, D-glucofuranuronic acid 0.56, 4-oxo-2-thioxo-3-thiozolidinepropionic acid 0.79, 1-Naphtalenemethanol 95.62, Patchoulene 0.27, D-mannitol 0.51, Threitol 0.86, Glycerol 0.86 (Syamsudin et al 2009). Preparations of propolis extract consisted of three phases including drying, extracting, and evaporating.…”
Section: Methodsmentioning
confidence: 99%